IMPLEMENTASI STANDAR SARANA DAN PRASARANA PENDIDIKAN PADA MADRASAH ALIYAH NEGERI 3 BANYUWANGI - Siti Aimah; Kholisatur Rohmah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
The objectives set in this study are: (1) To find out the implementation of Sarpras standards in MAN 3 Banyuwangi; (2) To find out the factors that are the strengths and weaknesses in implementing the standard of education sarpras at MAN 3 Banyuwangi; (3) To find out what factors are the weaknesses in applying educational infrastructure standards in MAN 3 Banyuwangi; (3) To find out the right strategy to be applied in MAN 3 Banyuwangi. This research method uses descriptive qualitative, data collection through interviews, observation and documentation. Data analysis using SWOT analysis and data validity techniques using triangulation. The results of his research: (1) Implementation of standard facilities and infrastructure at MAN 3 Banyuwangi, namely the suitability of facilities and infrastructure at the educational unit level MAN 3 Banyuwangi has 27 study groups. This is in accordance with the standards of Permendiknas Number 24 of 2007 which states that